(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Socks and underwear emit unpleasant odor, especially after they have been worn for long durations under certain conditions. This paper discusses the deodorizing properties of several typical fibers such as deodorizing acrylic, wool, line, cotton, Modal® and polyester fibers by instrumental testing. The odor from the socks made of these fibers after a one-day wear in summer is further evaluated by three testers using a human olfactory test. The molecular structure of the deodorizing acrylic fiber was confirmed by infrared spectroscopy. In terms of the deodorizing property of the various fibers with respect to ammonia, it is found that the deodorizing acrylic fiber had the best performance. This is attributed to the carboxyl groups in its molecular structure. Wool, Modal®, cotton, and linen fibers were worse in turn; polyester fibers had the worst performance. The absorption of acetic acid by wool, linen, and deodorizing acrylic fibers was better, followed by Modal® and cotton fibers. The polyester fibers, once again, had the worst performance. Thicker socks diffuse less odor than thinner socks made from the same fibers. The results of chemical analysis and sensory analysis show that the deodorizing performance of deodorizing acrylic fibers is superior.